Amish Secrets: Love Bears all Things - Book 2 - Wiseman, Beth, 1962- (Nashville, Tennessee : Thomas Nelson, 2016)
"Charlotte returns to her friends in Paradise, Pennsylvania--this time with a very different mission in mind. Englischer Charlotte Dolinsky makes plans to visit her friends in Lancaster County, hoping to heal from a recent break-up with her boyfriend, Ryan. But when a surprise visitor shows up on her doorstep in Texas, shes forced to put aside her own worries to help her Amish friends. Within a few days, Charlotte is back in Paradise, Pennsylvania, tangled in a web of deception. But this time, she isnt the only one keeping secrets. Daniel Byler had hoped to be married by now, but his one true love--Edna Glick--married another man. He gets through each day with a chip on his shoulder. But when Daniel finds out two members of his family are keeping secrets, he fears for his loved ones--fears of a shunning--and possibly even death. Charlotte and Daniel dont care for each other much, and neither one of them is looking for romance. But when they are forced to combine their efforts to help those they love, is it possible that God is giving them a second chance at happiness?"--
Keywords: Amish -- Fiction; Family secrets -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Romance fiction